Curative-intent surgery for isolated locoregional recurrence of colon cancer: Review of the literature and institutional experience. Issue 9 (September 2020) - Wisselink, D.D.; Klaver, C.E.L.; Hompes, R.; Bemelman, W.A.; Tanis, P.J.
Abstract: Background: Locoregional recurrence of colon cancer (LRCC) following curative resection is an underreported clinical entity, especially regarding isolated LRCC which is amenable for surgery. The purpose of this study was to review the literature on incidence of LRCC and surgical treatment with corresponding outcome, and to describe an institutional experience with curative-intent surgery, whether or not as part of a multimodality approach. Methods: The PubMed and Medline literature databases 1978–2017 were searched and retrieved articles were assessed for eligibility. Based on a prospectively maintained database since 2010 at a tertiary referral center, original patient files were retrospectively reviewed. Results: Systematic literature review resulted in 11 studies reporting on incidence of LRCC, which ranged from 3.1% to 19.0% before 2010, and from 4.4% to 6.7% in three most recent studies. Twelve identified studies reported on outcome of surgically treated LRCC, with a median survival of 30 and 33 months in the two largest studies. The institutional database entailed 17 patients who underwent resection of isolated LRCC between 2010 and 2018. Median time to recurrence was 19 months. After a median follow-up after resection of LRCC of 20 months, 7 patients had died, 9 patients were alive without evidence of disease and 1 patient with evidence of disease; Median DFS was 36 months and 3-year OS was 65%. Conclusion: Locoregional recurrence of colon cancer occurs in about 5% in most recent series, of whom selected patients are eligible for surgical treatment, with a fair chance of long-term disease control.